Numerical simulation of the nonstationary burning of a solid propellant in the combustion chamber of a controllable solid-propellant propulsion system - Krainov, Alexey Yu (Journal of engineering physics and thermophysics)
The nonstationary burning of a solid propellant in the combustion chamber of a controllable solid-propellant propulsion system under the conditions where the pressure in this chamber changes was simulated on the basis of the conjugate physical-mathematical model of the burning of a ballistic powder with regard for the processes proceeding in the condensed and gas phases of the solid propellant at the fourth-kind boundary conditions on the surface of its charge. Quantitative data on the deviation of the dynamic parameters of the gas in the combustion chamber of such a system from the experimental ones in the case where these parameters are calculated with account of the nonstationarity of burning of a solid-propellant charge in it and in the case where the quasistationary burning law is used for determining the dependence of the rate of burning of this charge on the pressure in the combustion chamber have been obtained.